Formulasi Dan Uji Efektivitas Sediaan Salep Ekstrak Etanol Daun Sintrong (Crassocephalum crepidioides (Benth.) S.Moore) Terhadap Penyembuhan Luka Bakar Pada Marmut Jantan (Cavia porcellus) - Muharni Saputri; Yessi Febriani; Olyvia putri Olyvia putri (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Background; Scar tissue formation due to infectious burns causes delayed maturation of the epidermis. Sintrong contains flavonoids, alkaloids, glycosides, saponins, tannins, and steroids which have anti-inflammatory and antioxidant functions and can protect the body from the harmful effects of free radicals. Preparations with good titration and long exposure times are needed to treat burn problems. This study aims to determine the process of making sintrong leaf ointment (Crassocephalum crepidiodes (Benth.) S.Moore) and the effect of treating burns from sintrong leaf extract in an ointment preparation that has been tested on male guinea pigs (Cavia porcellus). Methods; In this study, test methods were used by means of simplicia preparation, characterization, test phytochemical screening, extraction, formulation and adjustment of ointment preparations to concentrations of 0.5%, 1% and 1.5%, as well as evaluation of ointment tests which included stability tests, sensory tests, homogeneity tests,adhesion, spreadability, pH test, irritation test and efficacy test of ointment preparations. The results obtained from the characteristic examination indicate that the simplicia of the sintrong leaf has fulfilled the requirements of the characteristic test for simplicia. Result; The results of the phytochemical test showed that the positive sintrong leaves contained alkaloids, flavonoids, glycosides, saponins, tannins and triterpenes or steroids. The results of the evaluation of the ethanol extract of sintrong leaf ointment for stable results. The best formulation is formula 3 with a concentration of 1.5% with a wound healing diameter of 0.13 cm on the 21st day